Use of Social Media to Support Housewives' Steamed Bun Business - Raisa Namaga (Journal of Universal Community Empowerment Provision, 2023)
This thesis paper looks at how housewives can use online communities to promote their steamed bun enterprises. Social media platforms were chosen and accounts created, material was developed, posted, and engaged with, and analytics and metrics were gathered. Housewives were able to expand their customer base, gain more followers, and promote their products and services with the help of a well-thought-out social media strategy. Advertising on social media and forming partnerships with influential users boosted brand awareness and, in turn, sales. The study concluded that social media is an interesting topic worthy of future investigation because of its potential to aid small enterprises and enhance housewives' incomes. Thesis report keywords: steamed buns, housewives, and social media.